Analysis of Calculation of Value Added Tax Deposit and Reporting with E-Invoice System - Anisa, Nur Aini; Utomo, Priyo; Apriliasari, Ria Dini (Universitas Bhayangkara Surabaya, 2025)
This research uses two Value Added Tax data, namely, input of Value Added Tax data, along with output Value Added Tax data and sales data in 2024. The type of research is a qualitative approach, analysis uses descriptive data that aims to analyze data on various conditions and situations that arise based the object of research using sales data, input VAT and output VAT for the 2024 period of PT. XYZ Surabaya. While the data source in this study uses secondary data. From the results of the research that has been carried out, it shows that calculation, deposit and report of Value Added Tax carried out by PT. XYZ shows that the calculation, deposit and reporting of VAT using e-invoices are in accordance with Law No. 42 of 2009 concerning Value Added Tax (VAT) and Sales Tax on Luxury Goods (PPnBM).